The Generative Artificial Intelligence and the Changes in Political Economy - Prodanov, Hristo (Research Papers, 2024)
The study aims to explore the economic and political consequences of the introduction of generative artificial intelligence, characterized by its ability to create any type of content. Its object is the generative artificial intelligence, and the subject is about the changes it brings to economy and politics. Politico-economic approach is applied to investigate the interactions of technology with the economy and politics. It is based on the understanding that changes in technology depend on politics and economics, but at the same time they cause changes in both. The study begins with the definition of generative artificial intelligence and its differences from other types of artificial intelligence, what it can do and what its limitations are. The implications for the economy, production, exchange, distribution, consumption are then considered. The questions about the prospects, fears, social controversies it brings are also analyzed. It ends with the role of politics in the development, regulation, limitation, implication, management of generative artificial intelligence, because the social contradictions it brings might become dangerous for the society and politics. The scope of the research is global, and from this comes the main conclusion that the development of artificial intelligence is a global problem that requires global solutions.